Comparison between a novel sirolimus-eluting bioresorbable scaffold with everolimus-eluting metallic stent in patients with coronary artery disease: three-year follow-up from the neovas rct study. (14th October 2021) - Han, Y; Xu, K; Xu, B; Fu, G; Wang, X; Li, Y; Stone, G; ,
Abstract: Background: Previous trials and meta-analyses have demonstrated that risk of adverse clinical events, especially thrombosis and target vessel myocardial infarction is increasing between 1 and 3 years after Bioresorbable Scaffolds (BRS) implantation. Purpose: We sought to evaluate the long-term clinical outcomes of a novel NeoVas BRS in comparison with cobalt chromium everolimus-eluting stent (EES) following implantation in patients with coronary artery disease by 3-year follow-up results from the NeoVas RCT. Methods: Overall, 560 patients with a single de novo native coronary artery lesion with reference vessel diameter 2.5–3.75 mm and lesion length ≤20 mm were randomized 1:1 to NeoVas BRS vs. cobalt-chromium everolimus-eluting stents (CoCr-EES). Optical coherence tomography (OCT) and fractional flow reserve (FFR) were both performed in a pre-specified subgroup at 3-year follow-up. Clinical outcomes from NeoVas RCT were analyzed by randomized device (intention to treat) cumulative to 3 years. Results: Over 3 years, the overall target lesion failure (TLF) rate was 6.9% in the NeoVas group and 6.1% in the CoCr-EES group (HR 1.13, 95% CI 0.59 to 2.18; p=0.71). There was no statistically significant difference of the definite or probable stent thrombosis between the NeoVas group and the CoCr-EES group (1.1% vs. 0.7%, HR 1.51, 95% CI 0.26 to 8.73, p=0.64). In a landmark analysis of TLF, we found no difference in rate of late events from 2 to 3 years between two groups. FFR was not significantly different between the two group at 3 years (NeoVas vs. CoCr-EES, 0.89±0.07 vs. 0.90±0.05). NeoVas was largely absorbed (72.26% ± 13.21%) examined by OCT follow-up. Of 55 patients who finished 3-year absorption analysis, NeoVas was totally absorbed in 4 patients. Conclusions: At the 3-year follow-up in the Neovas RCT trial, overall TLF rates were comparable between Neovas BRS and CoCr-EES, and adverse event rates relating to device safety were not increased with Neovas BRS compared with CoCr-EES up to 3 years after implantation. Funding Acknowledgement: Type of funding sources: None.